Social Distancing as a Recontextualization of Filipino Values and Catholic Religious Practices: A Response to the COVID-19 Pandemic - Galang, Joseph Renus F. (Journal of religion and health, 2021)
This paper investigates Catholic religious practices and Filipino values in the Philippines during the COVID-19 pandemic. It aims to show that religious practices conducted with proper social distancing help in the development of a renewed understanding of Filipino values without contributing to the spread of the virus. This qualitative study makes use of expository writing and content analysis. First, religious practices before the pandemic marked by maximum social interaction are presented. Then, the paper shows religious practices during the pandemic marked by social distancing. Thirdly, the paper looks into how Filipino values are recontextualized in relation to religious practices despite the need for social distancing during the COVID-19 pandemic. Ultimately, the researchers claim that those who participate in religious practices with social distancing do not contribute to the transmission of the virus while still developing a renewed understanding of Filipino values.